ChemInform Abstract: FeCl3‐Catalyzed Cyclization of α‐Sulfonamido‐Allenes with Aldehydes — The Substituent Effect. Issue 16 (28th March 2013) - Cheng, Jiajia; Tang, Xinjun; Yu, Yihua; Ma, Shengming
Abstract The FeCl3‐mediated aza‐Prins‐cyclization reaction of α‐sulfonamido‐allenes (I) and (VI) with aldehydes affords selectively tetrahydropyridine (III) or dihydropyrrole derivatives (VIII), respectively.